KANDUNGAN LOGAM BERAT TIMBAL (Pb) PADA BAHAN BAKU AIR UNTUK PRODUKSI GARAM DI KAWASAN LADANG GARAM SEDAYULAWAS LAMONGAN - Hilda Ziya Abiyana; Mahmiah (Universitas Hang Tuah, 2021)
The waters of Sedayu Lawas Lamongan are widely used as salt production sites. Salt production is strongly influenced by the quality of raw water used. The quality of water raw materials must be free from heavy metal pollutants or in accordance with the threshold value (NAB). One of the heavy metals that pollute the environment is Lead (Pb). This study aims to analyze the heavy metal content of Pb in water raw materials, how the quality of raw materials of water when compared with quality standards and how the correlation between water physics-chemical parameters include rainfall, wind, temperature, salinity, pH to Pb content in 5 stations observation. The heavy metal content of Pb was analyzed by the Inductively Coupled Plasma-Optical Emission Spectrophotometer (ICP-EOS) method. Correlation using Pearson method. The results showed that Pb content of raw water for salt production in five stations was 0.0626, 0.0672, 0.0455, 0.0487, and 0.0416 ppm, respectively. Based on the measurement results when compared with the Ministerial Decree No. 51 Year 2004, the raw material of water used exceeds NAB which is 0.008 ppm. The result of parameter correlation to Pb content shows salinity, pH, has a strong inversely relationship affecting the presence of heavy metals. The temperature parameter has a direct relationship to the Pb content